2011
DOI: 10.1007/s10194-011-0346-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-infectious headache: a reactive headache?

Abstract: Post-infectious disease syndrome includes both neurological and non-neurological disorders. However, headache as an isolated or a presenting complaint of post-infectious illness has not been well acknowledged in the literature. In this retrospective observation, patients having daily headache of more than 1 week and <4 weeks duration were included. We divided this group into patients having headache with preceding history of febrile illness in the recent past and patients without such history of febrile illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Chronic post‐viral meningitis headache has not yet been proposed and is not a well‐reported entity . The appendix of the ICHD‐2 proposes an entity entitled “chronic post‐non‐bacterial infection headache.” Persistent headache after viral meningitis was described in a large series by Neufeld et al .…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic post‐viral meningitis headache has not yet been proposed and is not a well‐reported entity . The appendix of the ICHD‐2 proposes an entity entitled “chronic post‐non‐bacterial infection headache.” Persistent headache after viral meningitis was described in a large series by Neufeld et al .…”
Section: Expert Opinionmentioning
confidence: 99%
“…18 Chronic post-viral meningitis headache has not yet been proposed and is not a well-reported entity. 19 The appendix of the ICHD-2 proposes an entity entitled "chronic post-non-bacterial infection headache." Persistent headache after viral meningitis was described in a large series by Neufeld et al 20 In their study, 19 of 70 (27%) patients with meningitis developed post-meningitis headache, of whom 17 (89%) had aseptic/viral meningitis.…”
Section: Expert Opinionmentioning
confidence: 99%
“…In a retrospective study on patients with subacute daily headache (1-4 weeks durations), we observed that patients with a prior history of febrile illness are more likely to have neck pain and signs of meningismus (in addition to headache). 4 Our observation, 4 Almazov and Brand's observation, 2 and a few other observations 5 suggest a possibility of postinfectious pathology (most likely immunological) in meninges in patients who have a prior history of infections before the onset of headache. We further suggest that the interrelation between meninges and infections may be like the interrelation of synovial membrane to various viral infections for the development of reactive arthritis, as synovial membranes and meninges are of same type of tissue (membranous connective tissue).…”
Section: New Daily Persistent Headache: Disease or Syndrome?mentioning
confidence: 50%
“…An inherent difficulty is that NDPH is only diagnosed after being present for at least 3 months, and capturing these patients in the subacute time frame may yield the most insights; so we applaud Dr. Prakash's contributions to this endeavor. 11 Matthew S. Robbins, MD, FAHS Montefiore Headache Center, Saul R. Korey Department of Neurology, Albert Einstein College of Medicine, Bronx, NY, USA…”
Section: Response Letter: New Daily Persistent Headache: Disease or Smentioning
confidence: 99%